THE INEQUALITIES OF HELDER AND MINKOVSKY AND THEIR GENERALIZATIONS: НЕРІВНОСТІ ГЕЛЬДЕРА ТА МІНКОВСЬКОГО ТА ЇХНІ УЗАГАЛЬНЕННЯ - Bokhonov, Yuriy (Physical and Mathematical Education, 2025)
Formulation of the Problem. A large amount of mathematical literature is devoted to classical inequalities. Helder’s inequalities, a special case of which is the Cauchy-Buniakovsky inequality, as well as Minkowski’s, which is a polygon inequality in a normed space, underlie the geometry of unitary and normed spaces - finite and infinite-dimensional (Banach). The article considers the generalization of these constructions - both in discrete form, that is, for finite sums and series, and for integrals. It is essential that inequalities for sums are proved by elementary methods, without the use of differential calculus. The results obtained can be used in scientific activities for evaluating some expressions in the form of sums or integrals, as well as by students in preparation for Olympiads and even for studying mathematics in school circles. Materials and Methods. To prove the generalized Minkowski inequality and the integral inequalities of Helder and Minkowski, the generalized Helder inequality for sums, which was previously obtained by the author which, in turn, was derived from Cauchy’s inequality. Results. The generalized Minkowski inequalities were proved for finite sums and infinite series with non-negative members and the integral for non-negative functions, as well as the generalized integral Helder inequality and, in a special case, the Cauchy-Bunyakovsky inequality. Conclusion. The application of the generalized Helder and Minkowski inequalities for sums, series, and integrals is a fairly effective method that allows you to obtain interesting consequences, important estimates – you only need to successfully select finite-dimensional or infinite-dimensional vectors or functions and apply the proved inequalities to them. On this path, there is a great deal of space for creative activity.